1985
DOI: 10.1063/1.335959
|View full text |Cite
|
Sign up to set email alerts
|

High responsivity HgCdTe heterojunction photoconductor

Abstract: We present an experimental and theoretical study of n-type Hg1−xCdxTe photoconductors in which a large band-gap alloy was grown on top of a smaller band-gap active region and contacts were made to the larger gap material. The larger band-gap material causes an energy barrier to holes which decreases the rate at which they reach the high recombination region of the metal-semiconductor interface. As a result, this heterojunction contact greatly reduces the effects of carrier sweepout on device performance and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…In Fig. The minimum compositional difference, for the heterojunction to provide the bulk with effective shielding from surface effects, has previously been reported as being approximately 0.04, 12 which is close to the 0.06 value in hetwafer#1. Figure 5 also shows a device from hetwafer#2 that has poorer performance than typically obtained.…”
Section: And Discussionsupporting
confidence: 68%
“…In Fig. The minimum compositional difference, for the heterojunction to provide the bulk with effective shielding from surface effects, has previously been reported as being approximately 0.04, 12 which is close to the 0.06 value in hetwafer#1. Figure 5 also shows a device from hetwafer#2 that has poorer performance than typically obtained.…”
Section: And Discussionsupporting
confidence: 68%
“…Since CdTe is not lattice matched to narrow gap Hg 1−x Cd x Te, a heterostructure device has been proposed [31][32][33][34]. The device (figure 2) consists of an epitaxially grown layer of LWIR absorbing n-type MCT capped by a layer of wider bandgap n-type Hg 1−x Cd x Te.…”
Section: Wide Bandgap Capping Layermentioning
confidence: 99%
“…The structure does not need any additional passivant deposition. Calculations have shown that an Hg 1−x Cd x Te heterostructure with a change in the gap of x ≥ 0.04 is sufficient to prevent photogenerated carriers from reaching the regions of enhanced recombination [32][33][34]. In MCT photoconductive detector technology, the sidewalls are not fully passivated and hence the device sidewalls can become regions of high minority carrier recombination.…”
Section: Wide Bandgap Capping Layermentioning
confidence: 99%
“…The metal contacts are then made to the wider-bandgap HgCdTe which provides an energy barrier in the valence band that restricts the flow of minority carrier holes to the high-recombination region at the metal/semiconductor interface. As a result, the widerbandgap layer significantly reduces the effects of carrier sweepout at high bias fields, and provides over an order of magnitude increase in device responsivity in comparison to PC devices in which sweepout is predominant [11]. Alternatively, the same performance specification can be achieved by the HCP at a much lower bias level, which equates to lower power dissipation in the device.…”
Section: Review Of Current Pc Hgcdte Detector Technologymentioning
confidence: 99%
“…Two-dimensional arrays of PC detectors were fabricated on single-layer x = 0.23 n-type HgCdTe using the procedure outlined in section 3. Note that because of the absence of a wider-bandgap blocking/barrier layer, these devices will not exhibit the enhanced performance that has been demonstrated previously as being achievable with the use of two-layer heterostructure materials [11]. The wafers were purchased from Fermionics Corporation and consisted of an LPE grown HgCdTe layer on an insulating CdZnTe substrate.…”
Section: Experimental Array Performancementioning
confidence: 99%